If ((sqrt2x))/((sqrt3x - 1)) = 3/2, solve for x. Express your answer as a simplified fraction.

Guest Feb 20, 2018

#1**0 **

Solve for x:

(sqrt(2) sqrt(x))/(sqrt(3) sqrt(x) - 1) = 3/2

Cross multiply:

2 sqrt(2) sqrt(x) = 3 (sqrt(3) sqrt(x) - 1)

Subtract 3 sqrt(3) sqrt(x) from both sides and collect in terms of sqrt(x):

(2 sqrt(2) - 3 sqrt(3)) sqrt(x) = -3

Divide both sides by 2 sqrt(2) - 3 sqrt(3):

sqrt(x) = -3/(2 sqrt(2) - 3 sqrt(3))

Raise both sides to the power of two:

x = 9/(2 sqrt(2) - 3 sqrt(3))^2 =** 315/361 + (108 sqrt(6))/361**

Guest Feb 20, 2018